Signatures of hadronic cosmic rays in starbursts? : high-energy photons and neutrinos from NGC 253 - Romero, Gustavo Esteban (2003)
We show that it appears possible for starburst galaxies, like the nearby NGC 253, recently identified as a TeV source by the CANGAROO collaboration, to emit a significant amount of high-energy γ-rays and neutrinos through hadronic processes in their cores. We suggest that proton illumination of the inner winds of massive stars can be a viable mechanism for producing TeV γ-rays and neutrinos without a strong MeV-GeV counterpart. The rich stellar content of the starbursts, with millions of early-type stars concentrated in the central regions, where collective effects of the stellar winds and supernovae can produce a significant enhancement of the cosmic-ray density, provides an adequate scenario for TeV γ-ray generation. Close starbursts are also found to be potential sources for kilometer-scale neutrino telescopes, like IceCube, within reasonable integration times.